Siberia’s Development Th eories: A Curse or a Treasure? - D. V. Egorov (Сравнительная политика, 2015)
Th e article analyses 5 publications focused on Siberia’s development. It touches upon the problems of resource course, spatial reorganization of Russian economy, Siberia’s small or, on the contrary, huge population